Hydrogen-assisted failure in partially recrystallized carbon alloyed equiatomic CoCrFeMnNi high-entropy alloy. (15th July 2022) - Luo, Hong; Pan, Zhimin; Wang, Xuefei; Cheng, Hongxu; Nazarov, Ayrat A.; Li, Xiaogang
Abstract: We investigated the hydrogen-assisted failure behavior of partially recrystallized carbon alloyed equiatomic CoCrFeMnNi high-entropy alloys. Microstructural evolution in the vicinity of the crack initiation sites and propagation pathways was observed. The results showed that fracture of the samples in the presence of hydrogen was dominated by localized plastic deformation. Hydrogen enhanced nanotwinning and the formation of nanovoids were observed during tensile deformation. Furthermore, stress assisted intergranular and transgranular cracking in hydrogen-charged samples was caused by slip localization at boundaries. Observations confirmed that the resistance to hydrogen embrittlement was increased by the presence of non-recrystallized zones and nanotwins. Highlights: The hydrogen-assisted failure in partially recrystallized carbon alloyed equiatomic CoCrFeMnNi HEA (c-HEA) was investigated. The failure mode of the c-HEA was observed via multi-scale EBSD-ECCI. The relationship between the microstructure and hydrogen embrittlement was presented.